Cover Feature: Color Tuning in Garnet Oxides: The Role of Tetrahedral Coordination Geometry for 3 d Metal Ions and Ligand–Metal Charge Transfer (Band‐Gap Manipulation) (Chem. Asian J. 20/2017). Issue 20 (2nd October 2017) - Bhim, Anupam; Laha, Sourav; Gopalakrishnan, Jagannatha; Natarajan, Srinivasan
Abstract : New brightly colored garnet oxides : The substitution of 3d transition elements such as Co 2+ and Ni 2+ in the tetrahedral sites of garnet leads to different shades of blue colored compounds. The colors can be modified by simple band gap engineering of Fe 3+ substitution along with the Co 2+ and Ni 2+ in the tetrahedral site of garnet. The combined substitution of Fe 3+ and Co 2+ /Ni 2+ gives rise to shades of green and bluish green colored compounds. The strong exchange interactions between the localized d electrons of Fe 3+ and band electrons of Co 2+, Ni 2+ result in the band gap manipulation and color tuning in these garnets. More information can be found in the Full Paper by Jagannatha Gopalakrishnan, Srinivasan Natarajan et al. onpage 2734 in Issue 20, 2017 (DOI:10.1002/asia.201701040 ).